Forecasting the level of growth and development of root rots on Hordeum vulgare L. plants - Gentosh, D.; Havryliuk, L.; Bashta, O.; Olifer, D.; Artemchuk, I. (Quarantine and plant protection, 2025)
Goal. To develop short-term forecasting methods for the seasonal development of root rots of spring barley. Methods.The studies were carried out using correlation-regression analysis. Mathematical processing of the obtained data was performed using analysis of variance. Results. A high and statistically significant correlation was established between the indicators of spread and development of root rots of spring barley during the study period, as well as during the seasonal development of the disease in individual years. The obtained data show that when forecasting the level of infestation of spring barley with root rots, either one of the two indicators-disease spread or disease development-can be taken into account. The research analysis indicates that the maximum spread and development of root rot depend on the timing of the first visible symptoms. Statistical analysis shows a tendency for decreased spread and development of spring barley root rots when the first symptoms appear later in the season. As a result, the research enabled the development and construction of predictive models that allow determining the spread and development of spring barley root rots during the current season. Conclusions. The conducted analysis revealed that based on the average daily positive temperature, it is possible to reliably forecast the level of spread and development of spring barley root rots. Statistical analysis indicates a trend toward decreasing disease spread (r = –0.44) and development (r = –0.70) with a later onset of the first symptoms. The presented research data and statistical analysis provide comprehensive information on forecasting and regulating the phytopathogenic background in agrocenoses of spring barley, which is essential for modern agricultural production. This enables timely prediction of the onset or changes in the development of root rot diseases in plants.